Sociotechnical view of electric bike issues in China: Structured review and analysis of electric bike collisions using Rasmussen's risk management framework. Issue 6 (20th June 2021) - Wang, Linyang; Wu, Jianping; Liu, Mingyu; Hu, Kezhen; Plant, Katherine L.; McIlroy, Rich C.; Stanton, Neville A.
Abstract: Following a thriving delivery business and constantly improving road infrastructure and vehicle technologies, electric bicycles (e‐bikes) are becoming one of the most popular modes of road transport in China. Although e‐bikes are flexible and cost efficient, they contribute significantly to on‐road collisions in China. Therefore, this study focuses on the traffic safety of e‐bikes in China. Rather than following conventional engineering approaches, this study applies a sociotechnical analysis of the system, while focusing on the entities that significantly influence e‐bike safety. Applying Rasmussen's risk management framework (RMF) and its associated Accimap methodology shapes the systematic analysis of e‐bike collisions in China. This study identifies and discusses a general pattern of the contribution of social entities to e‐bike collisions. As such, the authors developed a generic model of e‐bike collisions in China. Couriers were considered important in this domain, and their status in the system was discussed. Moreover, recommendations have been proposed to improve e‐bike traffic safety in China.